Electrostatic ion beam trap for electron collision studies - Heber, O.; Witte, P. D.; Diner, A.; Bhushan, K. G.; Strasser, D.; Toker, Y.; Rappaport, M. L.; Ben-Itzhak, I.; Altstein, N.; Schwalm, D.; Wolf, A.; Zajfman, D. (My University, 2004)
We describe a system combining an ion beam trap and a low energy electron target in which the interaction between electrons and vibrationally cold molecular ions and clusters can be studied. The entire system uses only electrostatic fields for both trapping and focusing, thus being able to store particles without a mass limit. Preliminary results for the electron impact neutralization of C2− ions and aluminum clusters are presented.